Apple pomace as a source of phenolic compounds with potential application in cosmetic product - Alvarez Arraibi, Ana (2019)
Apple pomace is aby-product that might be considered as a competitive source ofalarge number ofbioactive compounds (particularly phenolic compounds) with potentially valuable applications. Interestingly, the maj or part ofthese bioactive compounds is found in apple peel, thereby becoming more concentrated in apple pomace when compared to the fresh fruit [l]. Phenolic compounds in apple pomace (e.g., hydroxycinnamic acids, flavonoids and dihydrochalcones) display health promoting activities, mainly based on their antioxidant, anti-inflammatory and antimicrobial properties [2]. Therefore, these compounds represent a promising cosmeceutical potential. In fact, apple polyphenols already showed to inhibit the fat production of sebaceous cells, making them appropriate to be used in anti-acne cosmetic formulations [3]. In the work described herein, apple pomace was dehydrated using two diflferent processes: oven drying (60 °C) and lyophilisation. Phenolic compounds were extracted from apple pomace using food grade solvents (water and ethanol) in different proportions. Phenolic compounds' profiles were further characterized by high performance liquid chromatography using a diode array detector coupled to a mass spectrometer. In what regarás dehydraüon process, lyophilized samples showed a higher number ofphenolic compounds, as also higher quantities of those detected in ali prepared extracts. The major phenolic compound was 5-0-cafFeoylquinic acid (»108 mg/100 g dw), but flavonoids, specifically flavan-3-ols, were also detected in significant leveis. Among these, four quercetin derivatives (differing in the sugar unit) and isorhamnetin-3-0- rutinoside were quantified in similar concentrations (»20 mg/100 g dw). The remaining compounds were 4-0-caífeoylquinic acid (»16 mg/100 g dw), B-type (epi)-catechin dimer, trimer and tetramer (»16 mg/100 g dw, »5 mg/100 g dw and »3 mg/100 g dw, respectively), and phloretin-2-O-xyloglucoside (»5 mg/100 gdw). Overall, the detected profiles raise the possibility of using apple pomace, which is a competitive starting material when compared to other natural matrices, as an alternative source ofthis type of phenolic compounds. Owing to their reported bioactivity, these compounds may further be included in diflFerent applications as exemplified by cosmetic formulations, considering their ability to inhibit fat production in sebaceous cells.